Water scarcity and livelihoods in Bihar and West Bengal, India. (2nd October 2018) - Ranganathan, Thiagu; Ranjan, Ram; Pradhan, Deepa
Abstract: Through a cross-sectional survey of 1600 households, we analyse the impact of water scarcity on livelihood patterns of rural households in three districts of Bihar and West Bengal. We find significant correlation between water scarcity and livelihood profiles. Households involved in farming and rural labour, or a mix of farming, rural labour and enterprises, earn 30–50% less than what they would have earned through alternative livelihoods. Yet, 50% of the sampled households were engaged in farming and rural labour. When accounting for endogeneity, urban migration provides much higher returns compared to rural labour supply or entrepreneurship.